Utveckling av konsultmatchningssystem - Vilppu,David; Blixt,Oscar (2022)
Wellbefy is a company that offers its customers a digital platform with the goal to increase wellbeing at workplaces. Through their platform and their users, they are obtaining data connected to areas in which problems often occur, such as sleep or stress. The platform can be used by anyone working at a company, from the boss to an employee. The problem with the current platform is that it can only be used to identify these problem areas.Wellbefy wants to further develop the platform and offer the users help to find solutions to the problems identified by the system. After participating in interviews and workshops with the management team of Wellbefy, a stand-alone system was developed in which a user can be presented with articles and consultants corresponding to that user’s identified problems. The system was delivered with a database, API, an admin-page, and a user-page. The main goal of this project is to study the most important methods and moments to build this system with a good user experience. This project also studies how to design and perform rewarding and useful user-tests to facilitate the development and design of the system.
Keywords: User Experience; Well-being; User test; Design process; Consulting matching system